Chemical exchange in two dimensions in the 1H NMR assignment of cytochrome c. - Feng, Y Q (1991)
The important role played by chemical exchange in solving the proton assignment problem for oxidized and reduced horse cytochrome c is described. Some novel approaches for establishing oxidation-reduction exchange correlations in combinations of several two-dimensional spectra were used. Unambiguous chemical exchange correlations were established for 55 NH-C alpha H resonances and all the aromatic and side chain methyl resonances. Consistent although not fully unambiguous main chain proton correlations were observed for 47 of the remaining 49 residues. The many exchange correlations found serve to multiply cross-connect the two extensive, individually self-consistent networks of assignments found for the oxidized and reduced forms, and thus help to confirm both sets of assignments.